Assessment of soil erosion and sediment yield in response to land use and land cover changes using geospatial techniques in Dumuga Watershed, Ethiopia - Zenebe Reta Roba; Mitiku Badasa Moisa; Sanju Purohit; Kiros Tsegay Deribew; Dessalegn Obsi Gemeda (All Earth)
Soil erosion and sediment yield driven by land use and land cover changes; pose severe threats to ecological sustainability, agricultural productivity, and watershed health. This study evaluates soil erosion and sediment yield in the Dumuga Watershed, Ethiopia, from 1993 to 2023, with a focus on the impact of land use and land cover changes. Utilising a time series of Landsat data (TM, ETM+, OLI/TIRS), the study analyzes key factors influencing erosion, including rainfall erosivity, soil erodibility, slope steepness, cover management, and conservation practice. The findings highlight a dramatic shift in land use, with cultivated land increasing from 62.3% (915.3 km2) to 77.0% (1,132.0 km2) and forest cover declining sharply from 13.3% (196.0 km2) to 3.8% (56.2 km2). This transformation has exacerbated erosion, with maximum soil loss rising from 726.7 tons/ha/year in 1993 to 937.8 tons/ha/year in 2023. The area classified under very severe erosion has increased from 41.0% to 54.1%, directly correlating with a rise in sediment yield. These findings underscore the urgent need for targeted soil conservation strategies to mitigate erosion, enhance sediment retention, and restore ecological balance. Therefore, implementing integrated land management approaches is essential to safeguarding the watershed’s long-term productivity and resilience.